2018
DOI: 10.5606/tftrd.2018.1896
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of Kinesio taping on pain and clinical features in chronic non-specific low back pain: A randomized controlled clinical trial

Abstract: Objectives: This study aims to investigate the effectiveness of Kinesio taping (KT) and sham KT on pain, lumbar range of motion (ROM) and disability in chronic non-specific low back pain. Patients and methods: This is a randomized, placebo controlled study. Sixty patients (22 males, 38 females; mean age 21.5±1.7 years, range, 19 to 25 years) with chronic low back pain were randomized into either intervention or placebo groups. Group 1 (n=30) was treated with KT and group 2 (n=30) was treated with sham taping s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…Some studies compared the effect of KT to placebo taping on pain and disability. In line with our findings, some studies showed that the levels of pain and disability significantly decreased after taping [18,[32][33][34], and some reported that KT is better than placebo taping in patients with CLBP [32,34,35]. On the other hand, some studies found no significant decrease in pain or disability after the intervention [36,37], and that the application of KT was not better than placebo taping for patients with CLBP [31,33,37], which is contradicted with our findings.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Some studies compared the effect of KT to placebo taping on pain and disability. In line with our findings, some studies showed that the levels of pain and disability significantly decreased after taping [18,[32][33][34], and some reported that KT is better than placebo taping in patients with CLBP [32,34,35]. On the other hand, some studies found no significant decrease in pain or disability after the intervention [36,37], and that the application of KT was not better than placebo taping for patients with CLBP [31,33,37], which is contradicted with our findings.…”
Section: Discussioncontrasting
confidence: 58%
“…The previous studies never evaluated the effects of KT on pain using SF-MPQ as a multidimensional tool in individuals with nonspecific CLBP, and they measured pain by VAS [18,32,34] or NRS [33,[35][36][37]. The current study is the first to assess the effects of KT on pain using SF-MPQ in individuals with nonspecific CLBP.…”
Section: Discussionmentioning
confidence: 94%
“…There were twenty-three RCTs related to conditions of the lumbar spine and abdominal wall, with all but one assessing KT (Appendix 2 File: Appendix 2G). One addressed KT for acute low back pain [136], two investigated KT for back pain in the setting of lumbar disc herniation [137,138], two investigated KT for pregnancy related low back pain [139,140], one RCT investigated postpartum diastasis recti abdominis [141], and sixteen investigated KT for chronic low back pain, [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157]. One study evaluated rigid taping for sacroiliac joint dysfunction [158].…”
Section: Lumbar Spinementioning
confidence: 99%
“…[ 10 12 ] KT is an elastic bonding material with high tensile capacity, which ensures the free movement of the application area without the need for chemicals. [ 13 ] KT can be extended to 140% of the original length, providing a good range of motion compared with other types of tape. Studies have shown that KT improves blood and lymph circulation, mitigates pain, adjusts joints, and relives muscle tension.…”
Section: Introductionmentioning
confidence: 99%